UNDERGRADUATES PERCEPTION OF CAUSES AND PREVENTION OF FAMILY VIOLENCE AMONG STUDENTS OF NNAMDI AZIKIWE UNIVERSITY, AWKA, ANAMBRA STATE - NWANKWO, C.U. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
The study aimed at determining the undergraduates' perception of causes and preventive measures of family violence. Prevention of violence in the family aimed at promoting social health of family members. Three research questions guide the study. Descriptive survey design was used ans a sample size of 315 undergraduate was obtained usimg simple random technique. Instructment for data collection was 44-item questions structured validated questionaire which was of modified likert-type of four-point rating scale. After administration of instrument, 300 copies were returned, correctly filled and same percieved causes and preventive measures for family violence by undergraduates. Based on the results, some recommendations were made, which if strictly followed can go a long way prevent family violence and promote soacial health